A novel antioxidant peptide derived from wheat germ prevents high glucose-induced oxidative stress in vascular smooth muscle cells in vitro. Issue 1 (6th December 2016) - Chen, Siyuan; Lin, Dingbo; Gao, Yulong; Cao, Xiaozhou; Shen, Xinchun
Abstract : A possible molecular mechanism of AOP in the inhibition of high glucose-induced ROS generation in VSMCs. Abstract : The ingestion of whole wheat products is responsible for the prevention of a number of chronic diseases. The aim of this study is to characterize the molecular properties of a novel wheat germ-derived antioxidant peptide (AOP) in protection against high glucose-induced oxidative stress in vascular smooth muscle cells (VSMCs). AOP (amino acid sequence AREGETVVPG) was isolated from wheat germ albumin using dual-enzymatic hydrolysis/separation, followed by MS/MS. The in vitro IC50 value for Fe 2+ chelation was 0.77 mM. The stability of purified AOP was confirmed by hydrolyzation in a simulated gastrointestinal (GI) digestion system in vitro . Furthermore, AOP significantly prevented high glucose-induced cell growth by 37.4 ± 2.7%, decreased the generation of intracellular reactive oxygen species (ROS) by 22.3 ± 4.6%, suppressed the phosphorylation of PKCζ, AKT and Erk1/2, and inhibited Nox4 protein expression. Our findings suggested that AOP exerted a protective role against high glucose-induced oxidative stress through the inhibition of the PKCζ/Nox4 signaling pathway in VSMCs.